Characteristics and effects of integrated nutrition and stimulation interventions to improve the nutritional status and development of children under 5 years of age: a systematic review and meta-analysis. Issue 7 (28th July 2021) - Dulal, Sophiya; Prost, Audrey; Karki, Surendra; Saville, Naomi; Merom, Dafna
Abstract : Introduction: Around 250 million children in low-income and middle-income countries are at risk of not fulfilling their developmental potential. There is a need to update syntheses investigating the effects of combined nutrition and stimulation interventions on children's growth and development and identify intervention characteristics associated with positive effects. Methods: We did a systematic review to: (1) understand the effects of integrated nutrition and stimulation interventions versus (i) usual care and (ii) standalone nutrition or stimulation interventions, on the growth and development of children under five; (2) explore intervention characteristics (delivery strategies, behaviour change techniques, intensity and personnel) associated with positive effects. We searched eight databases for studies published from inception to 16 November 2020. Eligible studies were randomised and non-randomised controlled trials of integrated nutrition and stimulation interventions examining growth and developmental outcomes. We performed meta-analyses for length-for-age/height-for-age, weight-for-age and weight-for-length/weight-for-height Z scores and cognitive, motor and language development scores, and subgroup analyses by intervention characteristics. We conducted random-effects metaregression to assess potential subgroup differences in outcomes by intervention characteristics. Results: Twenty trials were included in the meta-analysis. Pooled effect sizes showed significant benefits of integrated interventions on developmental outcomes compared with usual care and standalone nutrition interventions ( I 2 >75%) but not on growth outcomes. Moreover, integrated interventions have non-significant effects on developmental outcomes compared with standalone stimulation interventions. Integrated interventions showed greater effects on cognitive (p=0.039) and language (p=0.040) outcomes for undernourished children compared with adequately nourished children. The effects of integrated interventions on developmental outcomes did not differ by intervention characteristics. Conclusion: Integrated interventions have greater benefits for children's development than usual care or standalone nutrition interventions, especially in settings with high levels of undernutrition. Future studies should use standardised reporting of implementation processes to identify intervention characteristics linked to positive effects.